Theory does not meet experiment: transient dynamics changes patterns of exclusion in an intraguild predation system - Maciel, Gabriel Andreguetto [UNESP]; Kraenkel, Roberto André [UNESP] (Wiley, 2017)
Although empirical verifications of ecological theory are essential for the advance of our understanding of ecosystems functioning, they are often hard to obtain or even impractical. In this work we perform a detailed analysis of unexpected results found in a previous test of intraguild predation (IGP) theory. When the IG prey is the stronger competitor the IGP theory predicts a clear dynamical pattern along a resource gradient. In particular, the IG predator is expected to be excluded at low resources. In the experiment we analyze, IG prey was excluded at a resource level where the IG predator should be eliminated. We use a simple IGP model parametrized using mainly preliminary tests of the experiment. We suggest that experiment and theory agree if we look to the transient dynamics instead of asymptotic states, in which the usual theory is based. We show that extremely low IG prey populations during the transient may drive it to extinction and prevent the system from reaching long-term states. Our results are shown to be robust with respect to changes in initial conditions and parameters.
Keywords: Community modules; Population dynamics; Test of ecological theory; Transient exclusion